Recent and future developments in the legal regulation on rectifying sex assignment under law no. 164 of april 14, 1982. Notes in the margin of the constitutional court, july 23, 2024, no. 143. (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper analyses the evolution of domestic regulation in rectifying the attribution of sex provided by Law No. 164 of April 14, 1982, in light of the most recent rulings of the Constitutional Court. In view of the progressive elimination of the requirement for medical-surgical intervention for the legal recognition of gender identity, the paper addresses the relevance of psychological and social gender affirmation processes for rectification purposes, as well as the new need to protect non-binary individuals, arguing for the necessity of legislative intervention to introduce a third gender in civil status registration, in accordance with the personalist principle that underpins the legal system.
Keywords: gender identity; acts of bodily disposition; legal gender recognition; trans people; binarism